FAKTOR-FAKTOR YANG MEMPENGARUHI INVESTOR MEMILIH SAHAM SYARIAH (STUDI PADA GALERI INVESTASI DI SAMARINDA) - Yurdi Maulidani (Berkah Smart Academica, 2024)
The background of this research was to see the development of good stock transactions in Samarinda. Currently, Samarinda had 5 mediators to conduct stock transactions called the Investment Gallery. Basically the development of stock transactions was in line with the development of sharia shares in Indonesia. Investors are free to determine their decisions, choose sharia or non-sharia shares and the majority determines decisions on sharia shares which are based on the growth of sharia share transactions on the Indonesia Stock Exchange. The population in this research were all investors who had been registered in the Investment Gallery in Samarinda. The sampling technique used random sampling. The variables in this study were Religiosity Factors (X1), Cultural Factors (X2), Social Factors (X3), Personal Factors (X4), Psychological Factors (X5) and Investor Decisions (Y). Data collection techniques used observation, interviews and questionnaires. Test instrument used validity test (product moment) and reliability test (Cronbach Alpha) and classic assumption test (normality test, multicollinearity test, heteroscedasticity test and autocorrelation test). Method of descriptive data analysis used multiple linear regression, F test and t test. The results of the research showed that (1) the religiosity variable did not significantly influence investors' decision to choose sharia shares with tcount of 1.787 0.05. (2) Cultural variables affect the decisions of investors to choose sharia shares with tcount 1.990>ttable 1.988 and the significance value was 0.05≤0.05. (3) Social variables had no effect on investor decisions in choosing sharia shares with tcount 0.908 0.05. (4) Personal variables had no influence on investors' decisions in choosing sharia shares with tcount 0.393 0.05. (5) Psychological variables affect the decisions of investors in choosing sharia shares with tcount 4.316>ttable 1.988 and a significance value of 0.00≤ 0.05. (6) There was a positive and significant influence of religious, cultural, social, personal and psychological factors simultaneously on the decisions of investors in choosing sharia shares with a Fcount of 51.499>Ftable 2.32 and a significance value of 0.00.